Legal Dynamics of Environmental Governance within the Framework of Sustainable Development in Indonesia - Iskandar, Ivan; Pratiwi, Anna Desy; Budiman, Tji Natalia; Saedi, Hedi Ceril; Santoso, Edy (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
The primary factor posing a challenge to the implementation of environmental policies in Indonesia is weak law enforcement. Well-formulated environmental regulations are rendered ineffective when enforcement is weak and inconsistent. Numerous pollution cases end without meaningful legal consequences, either due to inadequate supervision or conflicts of interest between regulators and business actors. This study employs a normative–juridical approach with a normative legal research specification. Data analysis is conducted using a qualitative juridical method focusing on environmental law and sustainable development. The findings indicate that the implementation of environmental law in Indonesia has not been effective in supporting sustainable development. The main weaknesses lie in institutional limitations, inadequate supervision, and low levels of public participation. In addition, regulatory ambiguity and weak political commitment further hinder effective law enforcement. Therefore, strengthening institutional capacity, harmonizing regulatory frameworks, and integrating environmental considerations into development policies are essential to enable environmental law to function optimally.